2020
DOI: 10.1038/s41598-020-61469-2
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the botanical compounds to the pollinators Apis mellifera and Trigona hyalinata (Hymenoptera: Apidae)

Abstract: the toxicity of essential oils that can be used in insect pest management to pollinators needs further studies. Apis mellifera Linnaeus and Trigona hyalinata (Lepeletier) (Hymenoptera: Apidae) foragers were exposed by three pathways to ginger, mint, oregano and thyme essential oils to provide their Lc 50, LD 50 and Lc 90, LD 90 . oregano and thyme were more toxic through contact and topically for A. mellifera while the toxicity of mint and ginger was lower. Trigona hyalinata was more tolerant to the essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 53 publications
(62 reference statements)
1
19
0
Order By: Relevance
“…Composite films of ginger essential oil microcapsules were prepared according to the process described in Section 2.3.1. With the elongation at break and thickness as indexes and other test conditions remaining stable, we changed and studied gelatin addition (2,4,6,8, and 10 g/100 mL), gelatin:glycerin ratio (1:0.2, 1:0.3, 1:0.4, and 1:0.5) (w/w), microcapsule addition (0, 0.34, 0.85, 1.36, 1.87, and 2.38 g/100 mL) (w/w), and drying condition (20, 30, and 40 • C).…”
Section: Optimization Of Preparation Conditions Of Ginger Essential Oil Microcapsules Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite films of ginger essential oil microcapsules were prepared according to the process described in Section 2.3.1. With the elongation at break and thickness as indexes and other test conditions remaining stable, we changed and studied gelatin addition (2,4,6,8, and 10 g/100 mL), gelatin:glycerin ratio (1:0.2, 1:0.3, 1:0.4, and 1:0.5) (w/w), microcapsule addition (0, 0.34, 0.85, 1.36, 1.87, and 2.38 g/100 mL) (w/w), and drying condition (20, 30, and 40 • C).…”
Section: Optimization Of Preparation Conditions Of Ginger Essential Oil Microcapsules Filmsmentioning
confidence: 99%
“…Ginger oil has a strong inhibitory effect on Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Acinetobacter baumannii, and 30 multi-drug resistant A. baumannii clinical isolates [5]. Reportedly, spraying ginger essential oil on a plant's surface can shorten the residing time of pests and reduce the damage of pesticides to the environment and insects [6]. Ginger essential oil also has antibacterial and fresh-keeping effects on papaya that can help maintain its high quality [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thyme, thyme oil, and its principal active ingredient thymol have antimicrobial, antifungal, and insecticidal capabilities for pest control [28] . Reference to previous research by da Silva et al, [29] Apis mellifera Linnaeus (Hymenoptera: Apidae) were exposed to ginger, mint, oregano, and thyme essential oils across three pathways to determine their LC50, LD50, and LC90, LD90, oregano, and thyme were more harmful to (Apis mellifera L.) through contact and topically, whereas mint and ginger were less hazardous. In the present study, the effect of Thyme oil on fallen mites started strongly and significantly during the first day of treatment giving (19.66±2.90) then sharply declined till the last day of treatments (22 days) represented 1.66±0.66.…”
Section: Discussionmentioning
confidence: 99%
“…The current bee-essential oil literature may not be particularly helpful in selecting candidate essential oils to improve e-tent efficiency. Most previous studies have been limited to a few large-bodied, generalist, eusocial, non-groundnesting species (da Silva et al 2020;Thomas 2011;Balbuena et al 2012;Stopfer et al 1997;Denker et al 2010), making it difficult to extend their results to predominately small-bodied, solitary, ground-nesting species. In fact, a recent study found that eusocial stingless bees and honey bees spent less time in areas with essential (da Silva et al potentially suggesting that scents like spearmint may negatively affect capture rate in similar species.…”
Section: Discussionmentioning
confidence: 99%